Dynamic changes in the triacylglycerol composition and crystallization behavior of cocoa butter. (July 2020) - Yao, Yunping; Liu, Wentao; Zhang, Di; Li, Ruiting; Zhou, Hang; Li, Changmo; Wang, Shuo
Abstract: Dynamic changes in triacylglycerol composition during complete crystallization were investigated by separating crystals from molten cocoa butter (CB) over different lengths of crystallization time. The dynamic crystallization behavior of CB was described by solid fat content (SFC), crystal morphology, and microstructure. The crystallization process was divided into stages, based on the growth mode of crystals: the induction, primary crystallization, and secondary crystallization stages. As crystallization progressed, the relative content of 1, 3-dipalmitoyl-2-oleoylglycerol (POP) increased from 12.1% to 29.8%; that of 1, 3-distearoyl-2-oleoylglycerol (StOSt) decreased from 37.1% to 20.2%; and that of tristearin (StStSt) decreased from 4.9% to 0.2%. Circular crystals were formed at the induction and primary crystallization stages, and β′-III form and β′-IV form polymorphisms were exhibited. When crystallization entered the secondary crystallization stage, the crystal morphology changed from circular to acicular, and polymorphic transformation from the β′-III form and β′-IV form to the β-form was observed. Graphical abstract: Image 1 Highlights: Dynamic crystallization behavior of triacylglycerol in cocoa butter was explored. The crystallization process was divided into three stages based on growth mode. The melting point of seed crystals in cocoa butter was above 57 °C.